PERAN KELOMPOK TANI PEMBUDIDAYA IKAN âMINA PERKASAâ DALAM MENUNJANG KETAHANAN EKONOMI ANGGOTA KELOMPOK (STUDI DI PURWOMARTANI, KALASAN, SLEMAN, DI YOGYAKARTA) - , Abdul Haris Subarjo ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study is entitled as "The Role of Fish Farmers Group in the Economic Resilience of the Member Group Member, a case study on fish farmers " Mina Perkasa " in Purwomartani, Kalasan, Sleman". It was conducted with the aim of determining the activities undertaken by the fish farmers in fish farming, the constraints faced by fish farmers in developing its business, the role obtained from a unit of activities for the groups of fish farmers and with the aim of knowing the economic role of fish farming in supporting the family economic condition. This research is a descriptive analysis with qualitative and quantitative approaches. Type of this research was a survey research. The population in this study was the members of the fish farmers groups in Purwomartani, Kalasan, Sleman, Propinsi Daerah Istimewa Yogyakarta. The samples were taken by purposive sampling that was the fish farmers âMina Perkasaâ which has a membership of 31 people. This study used four data collection techniques which were observation, interview questionnaires, and literature. Quantitative data analysis techniques in the study were the analysis of the respondersâ poverty, which was based on the data of the respondentsâ revenues and expenditures. For the income data, it was used the standard conception of the poverty which refered to the BPS and Sayogjaâs poverty line consumption. The results of this study was that the âMina Perkasaâ fish farmersâ activities covered the purchase of seed, development (cultivation), harvest, marketing, and post harvest. The constraints encountered in developing the business were water and capital. The role of the groups was as a unit of study, a cooperative unit, a unit of production and a business unit. The economic role of fish farming was supporting the family economic condition with the contribution of fisheries to the revenues of 33.33%, with ouput-input analysis of 1,27. This is lower than the âMino Ngrembokoâ fish farmersâ output-input analysis, that is fish farmersâ in Bokesan, Ngemplak, Sleman of 4,56 output-input analysis.